Impact of use of illustration in the presentation of Neuroanatomy through the analyses of the illustration in the Neuroanatomy text books commonly used by the medical postgraduates of Bangladesh (Bangladesh Journal of Anatomy, 2013)
Bangladesh Journal of Anatomy, January 2012, Vol. 10 No. 1 pp 27-31 DOI: http://dx.doi.org/10.3329/bja.v10i1.15756